Strengthening students’ scientific literacy through scientific coaching programs - Umi Muzayanah; Arif Gunawan Santoso; Saimroh Saimroh; Titi Isnaini Fauzah (Institute of Advanced Engineering and Science, 2023)
The scientific literacy of madrasa students currently shows a very proud trend. This is shown by the achievements in the field of science obtained in various science competitions. Scientific achievements are obtained through a long and continuous process, including through science coaching. By using qualitative methods, this study aimed to describe the science coaching model at State Madrasah Aliyah (MAN) 2 Malang City. The results showed that the science coaching model in MAN 2 Malang City includes four main aspects. First, strengthening the management aspect through establishing the olympic and research program and fulfilling adequate infrastructure. Second, strengthening students’ concepts and abilities through matriculation and programmed guidance. Third, empowering the olympic class and the olympic club through a rigorous selection and the implementation of periodic tests and tryouts. Fourth, synergy with other parties, such as Ma’had Al-Qalam, state universities, and National Achievement Center (Pusat Prestasi Nasional/Puspresnas). The success of scientific development cannot be separated from the interest and motivation of students to learn, adequate infrastructure, a conducive learning environment, and the support of the madrasa principal, committee, and parents.